Investigation of PON1 activity and MDA levels in patients with epilepsy not receiving antiepileptic treatment - Dönmezdil N; Cevik MU; Ozdemir HH; Taşin M (Neuropsychiatric Disease and Treatment, 2016)
Nilüfer Dönmezdil, Mehmet Uğur Çevik, Hasan Hüseyin Özdemir, Muhterem Taşin Department of Neurology, Dicle University, Diyarbakır, Turkey Purpose: There are many studies dedicated to researching the etiopathogenesis of epilepsy. In such research, oxidative and antioxidant indicators of etiopathogenesis have also been examined under the scope. Drawing on a group of patients with epilepsy who were receiving no treatment, we have tried to evaluate whether or not an increase in oxidative indicators is linked directly with the disorder, independent of epileptic medicaments.Methods: Thirty people in good health and 30 newly diagnosed with epilepsy and who received ambulatory treatment in the polyclinic of the Neurology Department took part in the study. The tests relating to serum malondialdehyde (MDA) levels and paraoxonase 1 (PON1) activity were carried out in the biochemistry laboratory.Results: Even though the levels of MDA in the patient group (14.34±3.59 nmol/mL) were found to be high compared to those of the control group, which consisted of people in good health (13.53±3.56 nmol/mL), there was no statistically significant difference. PON1 activity in the serum taken from people in the patient group (0.65±0.17) was lower in comparison to that observed in the serum of the control group (0.71±0.17 U/L). Nonetheless, it was not so low as to have significance from a statistical point of view.Conclusion: We conclude that such a high level of oxidative parameters should have been related to the disease and that statistically significant findings that emerged in some other studies could have been related to an antiepileptic treatment. Keywords: epilepsy, paraoxonase 1, malondialdehyde, oxidative stress, epilepsy, biochemical marker